Reduction of pancreatic acinar cell tumor multiplicity in Dnmt1 hypomorphic mice - Oghamian, Shirley (Oxford University Press, 2011)
In human pancreatic cancers, promoter CpG island hypermethylation is observed in both benign and malignant tumors. It is thought that silencing of key growth-controlling genes by promoter hypermethylation may play a role in pancreatic oncogenesis. We have shown previously that sufficient levels of DNA methyltransferase (Dnmt) 1 expression are required for the development of murine intestinal tumors. Here, we report the results of a large-scale triple cross (progeny n = 761) between Apc(Min/+), Trp53(−/−) and Dnmt1 hypomorphic mice to investigate the role of Dnmt levels in the Apc(Min/+), Trp53(−/−) mouse models of acinar cell pancreatic cancer. Mutations of both APC and TP53 are observed in human pancreatic cancer. We found that tumor burden, but not tumor size, is significantly reduced with decreasing Dnmt1 levels, suggesting that DNA methylation is involved in pancreatic tumorigenesis in this mouse model. Detailed analyses showed that the reduction in tumor burden is the result of a decrease in both early- and late-stage lesions. We observed decreased levels of DNA methylation at candidate genes in the normal pancreas of Dnmt1 hypomorphic mice. Some of these genes showed increased methylation associated with tumorigenesis, suggesting that the tumor-suppressive effects of Dnmt1 hypomorphic alleles may be mediated in part through reduced promoter hypermethylation. Our work is the first in vivo study to show the effects of reduced Dnmt levels on pancreatic tumor development.